The system for assessing the competitiveness of oil refining organizations in terms of digitalization - Romanenkov N. V. (Science and education: future development, 2018)
This article discusses the generalized criteria and indicators for assessing the competitiveness of oil refining organizations. Proposed indicators that take into account the features of digitalization and formed an evaluation system.
Keywords: конкурентоспособность; competitiveness; digitalization; цифровизация; организации нефтепереработки; refining organizations